Pengembangan Aplikasi berbasis Thunkable Pemanah (Pembelajaran Mengenal Hijaiyah) beserta Harakatnya pada Pembelajaran Pai Kelas 1 SD - Nur Aeni, Ani; Nurfauziah, Maulina; Nadia, Luthfia; Priskia Putra, Wilki (STAI Terpadu Yogyakarta, 2024)
This research was conducted because of the limited number of innovative PAI learning media. Based on this problem, we developed an application to help students learn, especially about the hijaiyah letters and their simple harakat (fathah, kasrah, and dhammah) correctly. The research uses the Design and Development (D&D) method. This research was conducted to test and evaluate application products. The trial was carried out at Ranjeng State Elementary School. The research subjects were first grade students with a total of 25 students and we asked PAI teachers as material experts for their assessments. We obtained this data based on the results of the assessment when testing the application so that it succeeded in helping students not feel bored while viewing the application that we created. The purpose of this application trial is to see the feasibility of the application that has been created to help students learn hijaiyah letters and their simple harakat correctly. The results of this study show that more than 78.6% of teacher assessments and 98.8% of student assessments. So the PEMANAH application product is suitable for use in learning hijaiyah letters in elementary schools. Based on the research conducted, it was concluded that the PEMANAH application could be a solution as a medium for teaching PAI class 1 at Ranjeng State Elementary School.